Characterization of petite mutants of the basidiomycetes Phaffia rhodozyma CBS 5905 - Pfeiffer, Ilona (Acta Biologica Szegediensis, 2010)
Small, "petite" colonies appeared with almost 1% frequency among the normally growing colonies in the astaxanthin-producing Phaffia rhodozyma (Xanthophyllomyces dendrorhous) CBS 5905 strain. These colonies fermented glucose in the presence of oxygen, were not able to grow on nonfermentable carbon sources and did not respond to inhibitors of respiration. Besides spontaneous occurrence, petite mutation proved to be inducible almost to 100% by low levels of ethidium bromide treatment. Cell hybridization experiments revealed that both the spontaneous and induced mutation was mitochondrially inherited. The RFLP pattern of the mtDNAs isolated from purified mitochondria of the grand and petite strains were similar. Consequently, unlike to the mtDNA of Saccharomyces cerevisiae, not large deletions were the reason for petite mutant induction. The size of mtDNA in the grand cells was calculated by restriction enzyme analysis and proved approximately 17.6 kb. In teleomorphic strains of P. rhodozyma (Xanthophyllomyces dendrorhous) spontaneous petite mutants did not arise and the phenotype could not be induced either by ethidium bromide treatment. According to our results, Phaffia rhodozyma is the only known petite-positive basidiomycetous yeast.